Pengaruh Katekisasi Sidi terhadap Perubahan Perilaku Remaja Kristen di HKBP Kobun Kopi - Tumpal Richardo Sirait (Bulletin of Community Engagement, 2024)
The objective of this study is to investigate the impact of catechism sidi on the behavior of Christian adolescents at HKBP Kobun Kopi. By conducting an in-depth analysis, the study aims to provide a clearer understanding of the relationship between catechism sidi and the behavior of Christian adolescents and the potential for behavioral changes that may occur. A descriptive analytical research design with a cross-sectional approach was used in this study. Data was collected at a specific point in time to examine the relationship between catechism sidi variables and the behavior of Christian adolescents. The population of this study included Christian adolescents at HKBP Kobun Kopi who actively participated in catechism sidi. The sampling was conducted through purposive sampling, with the inclusion criteria being active Christian adolescents who had participated in catechism sidi for at least six months. The data analysis results revealed a significant influence of catechism sidi on the behavior of Christian adolescents at HKBP Kobun Kopi. The survey conducted showed that the majority of Christian adolescents who participated in catechism sidi demonstrated an increase in understanding of religious values and adherence to Christian teachings. Moreover, teenagers who regularly participated in catechism activities tended to exhibit more positive attitudes and behaviors in their daily lives, such as being more diligent in worship, more compassionate towards others, and better able to cope with pressure and temptations in their surroundings. The study concludes that catechism has a significant impact on the behavior of Christian adolescents at HKBP Kobun Kopi, as evidenced by the changes in behavior observed after participating in catechism. Additionally, the study's findings indicate that factors that influence the behavior of Christian teenagers can be moderated through catechism.